Knowledge, practise and atittude toward painkillers among patients at Pain Clinic in HUSM - Ahmed Bakhtiar Jamily, Ahmed Ali Bashir; Mat Razali, Mohammad Firdaus; Mat Jusoh, Muhammad Muhajir (2017)
We have studied the level knowledge, practise and attitudes among patients toward painkillers. Our study are focusing on patients' knowledge, practise and attitudes towards their painkillers and revealing many benefits. The study was conducted in Pain clinic in HUSM. This study seems to be significance to obtain statistic survey among the visitors in the clinic. Our study subjects are the visitors in the Pain clinic in HUSM on October 2016 until February 2017. They were chosen randomly between ages 18-70 and had been given a set of questionnaire for the assessment. Our focus on this study is to relate the patients' demographic data which is their age and gender with their knowledge, practise and attitudes towards their painkillers. We limit the data collection to only 200 respondents and manage to get all 200 questionnaire answered. The data then were explored by us and we key in accordingly to our desired analysis by using SPSS software version 16.0 and the results were presented in table and graph form. As expected by us, the male got higher knowledge on their painkillers compared to women while in age with practise and attitudes we found that patients, aged 31-40 are dominating with almost 200 respondents. Moreover, the results could be used to enhanced patients' compliance towards painkillers and pain management toward related institution.